Legends : the best players, games, and teams in baseball - Bryant, Howard, 1968- (Philomel Books, an imprint of Penguin Group (USA), 2015)
Presents a history of America's pastime that discusses many of its most notable players, teams, rivalries, and moments, from Jackie Robinson's breaking of the color barrier to the home run race between Sammy Sosa and Mark McGwire.